2022
DOI: 10.21070/pels.v2i0.1174
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Work Posture and Work-Related Musculoskeletal Disorders with ROSA Method at Batam Environmental Service

Abstract: Nowadays, computer is widely used in the work field. It is because computers can increase work efficiency and effectiveness. Dinas Lingkungan Hidup (DLH) Kota Batam facilitates its employees with computers to support their work activities in the office. The activity of using this computer is carried out in a sitting manner by office employees. Employees work posture such as sitting posture and duration of using computer which doesn’t pay attention to the ergonomic side can causing muscle pain called Work-Relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 10 publications
(9 reference statements)
0
2
0
2
Order By: Relevance
“…Doing awkward positions for hours in a day can also lead to muscle fatigue and stress because the body position tends to be the same as doing repetitive activities. [7] Research by Putri (2022) showed that based on the research on the working posture using the ROSA method, it was found that 4 of 6 Batam City Environmental Office workers scored more than 5, which meant that the workers' working postures were at risk. Muscle complaints (MSD) and the risky working posture indicated that improvement measures were needed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Doing awkward positions for hours in a day can also lead to muscle fatigue and stress because the body position tends to be the same as doing repetitive activities. [7] Research by Putri (2022) showed that based on the research on the working posture using the ROSA method, it was found that 4 of 6 Batam City Environmental Office workers scored more than 5, which meant that the workers' working postures were at risk. Muscle complaints (MSD) and the risky working posture indicated that improvement measures were needed.…”
Section: Resultsmentioning
confidence: 99%
“…Other interventions that can be carried out include the improvement of workers' posture and design facilities such as tables and chairs appropriate to the workers' anthropometric applying sitting concept. [8,9] Musculoskeletal disorders (MSD) become the highest contributor to work-related disease (penyakit akibat kerja -PAK) due to a lack of attention on the ergonomic work posture. This disorder played a role in the morbidity of some work areas and was known as an important work health problem since it increased health fund compensation, decreased the workers' productivity, decreased life quality, decided to move to other work, and even caused a disability for the workers.…”
Section: Resultsmentioning
confidence: 99%
“…Pekerjaan yang dilakukan berulang-ulang dengan sikap kerja yang tidak wajar dan peregangan otot berlebihan, serta dilakukan dalam durasi waktu yang Academics in Action Journal Volume 4, Number 1, 2022, 9--18 lama , yaitu empat sampai dengan delapan jam dapat menyebabkan terjadinya keluhan musculoskeletal (Dinar, Susilowati, Azwar, Indriyani, & Wirawan, 2018). Adanya keluhan otot yang dialami pekerja dan postur kerja yang berisiko ini mengindikasikan bahwa diperlukannya tindakan perbaikan (Putri & Amalia, 2021).…”
Section: Pendahuluanunclassified
“…The rapid development of information and communication technology (ICT) has reduced the use of pen and paper to a minimum (Yahfizam, 2019) [1]. Computer usage, considered non-ergonomic, can cause various problems, such as headaches, stress, muscle pain, and tension in the neck, back, arms, shoulders and other parts related to computer use [2]. Computer users or office workers often experience health problems related to musculoskeletal disorders, which can interfere with the functioning of muscles, tendons, nerves, blood vessels, bones, and ligaments due to a position considered uncomfortable.…”
Section: Introductionmentioning
confidence: 99%